Obesity-Associated Abdominal Elephantiasis - Ritesh Kohli; Vivian Argento; Yaw Amoateng-Adjepong (Case Reports in Medicine)
Abdominal elephantiasis is a rare entity. Abdominal elephantiasis is an uncommon, but deformative and progressive cutaneous disease caused by chronic lymphedema and recurrent streptococcal or Staphylococcus infections of the abdominal wall. We present 3 cases of patients with morbid obesity who presented to our hospital with abdominal wall swelling, thickening, erythema, and pain. The abdominal wall and legs were edematous, with cobblestone-like, thickened, hyperpigmented, and fissured plaques on the abdomen. Two patients had localised areas of skin erythema, tenderness, and increased warmth. There was purulent drainage from the abdominal wall in one patient. They were managed with antibiotics with some initial improvement. Meticulous skin care and local keratolytic treatment for the lesions were initiated with limited success due to their late presentation. All three patients refused surgical therapy. Conclusion. Early diagnosis is important for the treatment of abdominal elephantiasis and prevention of complications.